1986
DOI: 10.1021/bi00362a018
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosyliron(III) hemoglobin: autoreduction and spectroscopy

Abstract: Nitrosyl complexes of the iron(III) forms of myoglobin, human hemoglobin, Glycera dibranchiata hemoglobins (Hbm and Hbh), and model iron(II) and iron(III) synthetic porphyrins including octaethylporphyrin (OEP) have been prepared. The iron(III) heme proteins are electron spin (paramagnetic) resonance (ESR) silent, while hexacoordinate solution structures are indicated for [Fe(OEP)(NO)2]ClO4 and for Hbm(II)NO, which has an ESR spectrum similar to that of Mb(II)NO and the hexacoordinate iron(II) model complex Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 53 publications
8
95
1
Order By: Relevance
“…The observation of Wade and Castro (23) that met-Hb is extremely ineffective, as compared with, for example, horse metmyoglobin, in promoting the apparent nitrosation of exogenous nucleophiles may, in part, reflect interference from the intramolecular nitrosothiol-forming reaction. Our results also clarify certain observations of Addison and Stephanos (22), which were interpreted as indicating that the protein product obtained by complete reductive nitrosylation of methemoglobin is modified in the course of the reaction: Addison and Stephanos, however, suggested that this modification entails nitrosation of a histidine or lysine rather than the thiol. Finally, the variation of the levels of heme-Fe(II)NO hemoglobin complexes that have been detected in blood by EPR and other methods (33-40) may be influenced by the levels of heme-Fe(III)NO and other EPR undetectable species that can interchange with the heme Fe(II)NO species under different methods of sample treatment.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The observation of Wade and Castro (23) that met-Hb is extremely ineffective, as compared with, for example, horse metmyoglobin, in promoting the apparent nitrosation of exogenous nucleophiles may, in part, reflect interference from the intramolecular nitrosothiol-forming reaction. Our results also clarify certain observations of Addison and Stephanos (22), which were interpreted as indicating that the protein product obtained by complete reductive nitrosylation of methemoglobin is modified in the course of the reaction: Addison and Stephanos, however, suggested that this modification entails nitrosation of a histidine or lysine rather than the thiol. Finally, the variation of the levels of heme-Fe(II)NO hemoglobin complexes that have been detected in blood by EPR and other methods (33-40) may be influenced by the levels of heme-Fe(III)NO and other EPR undetectable species that can interchange with the heme Fe(II)NO species under different methods of sample treatment.…”
Section: Resultssupporting
confidence: 88%
“…Although the reductive nitrosylation of oxidized heme-proteins has been studied for Ͼ60 years (18)(19)(20)(21)(22)(23)(24), the reaction of NO with methemoglobin remains only partially understood. In the case of simple monomeric heme-proteins, reductive nitrosylation has been most simply summarized by the equation:…”
Section: Resultsmentioning
confidence: 99%
“…1B). The addition of NO to the Fe(III)-HRI complex resulted in a shift in the Soret peak to 398 nm, indicating reductive nitrosylation of the complex, leading to the formation of a Fe(II)-HRI(NO) complex (data not shown), as reported for Hb (26). The Soret band of the Fe(II)-HRI(NO) complex at around 400 nm is characteristic of a five-coordinate NO-heme complex, analogous to sGC (27), CBS (28), CooA (29), and cytochrome cЈ from denitrifying bacteria (30,31), and is distinct from spectra of the six-coordinate NO-heme, which contain Soret bands at around 415-425 nm (Table I).…”
Section: Resultssupporting
confidence: 60%
“…This suggests that coordination of the NO to the heme iron is similar in both hemoproteins, although the broader bandwidth observed with the hHO-1 complex suggests that the NO has greater mobility in that protein. Generally, as is the case for the binding of NO to ferric hemoproteins, these results strongly argue that the NO is bound perpendicular to the heme face rather than at an angle (53)(54)(55)(56), in contrast to its orientation when bound to ferrous hemoproteins. Furthermore, in both met-Mb and ferric hHO-1-heme, the iron in the absence of NO is coordinated to a water molecule.…”
Section: No Binding To Mutant Ferric Hho-1-heme Complexes-as Shown Inmentioning
confidence: 69%